THE AUTHOR’S LITERARY AND AESTHETIC VIEWS IN THE NOVEL "SEARCHERS OF PARADISE". - Rajabova, Marifat (FILOLOGIYA UFQLARI JURNALI, 2023)
This article is devoted to the Masters of the skill of using proverbs and sayings in the novel “golden stainless” of the 20th century writer Shukhrat. The article is based on the fact that the writer studied in depth the samples of the work of the people’s mouth when creating the novel. In particular, the fact that the writer was able to use proverbs and main phrases appropriately in the novel is given by analysis and interpretation through excerpts from the work. Shukhrat is proved that the good knowledge of folklore fully ensured the life output of the novel “golden stainless”.